Cultural Practices as a Tool for the Tourist Destination Development - Olha Kopiievska (Культура і мистецтво у сучасному світі)
The aim of the article is to analyse the functional peculiarities of cultural practices under the conditions of transforming tourist destinations in Ukraine. Results. On the basis of the conducted analysis, it is proved that the preservation of the uniqueness and attractiveness of tourist destinations depend on effective management and strategic priorities. It allows preserving the integrity of the cultural and tourist space with qualitatively new and attractive cultural practices. It is revealed that the tourist destination formation is one of the main tasks in the system of cultural policy development of modern states. The study analyses the role of tourist destinations as custodians of cultural heritage at all levels, such as global, glocal and local. It is established that such destinations form a unique cultural space for the entire country. They act as cultural receptacles and centres of cultural life that attract both local residents and tourists from other countries. It is noted that the symbiosis of cultural and tourist practices allows to form a national image with its unique cultural potential. The scientific novelty of the study consists in the theoretical understanding and determining the practical role and significance of cultural practices in the process of transforming tourist destinations. Conclusions. Ukrainian reality and world practices testify to active cultural transformations of tourist destinations. As custodians of cultural heritage, tourist destinations form the cultural space of the entire country. They are a concentration of cultures, a centre of cultural life of the state’s citizens, and a centre of tourism for representatives of other countries. An important tool for the qualitative transformation of the tourist destination functionality are cultural practices that are able to provide emotional recovery, establish rational communication and dialogue between all participants in the cultural process. As a cultural practice, intercultural dialogue is the most important value in solving the global problems of nowadays. The formation and development of a cultural landscape with unique cultural practices are the most important factors for preserving and restoring tourist destinations together with their values, which depend on national identity.